Exo-erythrocytic development of Plasmodium matutinum (lineage pLINN1) in a naturally infected roadkill fieldfare Turdus pilaris - Helene Pendl; Carolina Hernández-Lara; Jakub Kubacki; Nicole Borel; Sarah Albini; Gediminas Valkiūnas (Malaria Journal, 2022)
Abstract Background Species of Plasmodium (Haemosporida, Plasmodiidae) are remarkably diverse haemoparasites. Information on genetic diversity of avian malaria pathogens has been accumulating rapidly, however exo-erythrocytic development of these organisms remains insufficiently addressed. This is unfortunate because, contrary to Plasmodium species parasitizing mammals, the avian malaria parasites undergo several cycles of exo-erythrocytic development, often resulting in damage of various organs. Insufficient knowledge on the exo-erythrocytic development in most described Plasmodium species precludes the understanding of mechanisms of virulence during avian malaria. This study extends information on the exo-erythrocytic development of bird malaria parasites. Methods A roadkill fieldfare (Turdus pilaris) was sampled in Switzerland and examined using pathologic, cytologic, histologic, molecular and microbiologic methods. Avian malaria was diagnosed, and erythrocytic and exo-erythrocytic stages of the parasite were identified using morphologic characteristics and barcode DNA sequences of the cytochrome b gene. The species-specific characteristics were described, illustrated, and pathologic changes were reported. Results An infection with Plasmodium matutinum lineage pLINN1 was detected. Parasitaemia was relatively low (0.3%), with all erythrocytic stages (trophozoites, meronts and gametocytes) present in blood films. Most growing erythrocytic meronts were markedly vacuolated, which is a species-specific feature of this parasite’s development. Phanerozoites at different stages of maturation were seen in leukocytes, macrophages, and capillary endothelial cells in most organs examined; they were particularly numerous in the brain. Like the erythrocytic meronts, growing phanerozoites were markedly vacuolated. Conspicuous exo-erythrocytic development and maturation in leucocytes suggests that this fieldfare was not adapted to the infection and the parasite was capable to escape from cellular immunity. Conclusions This is the first report of exo-erythrocytic development of the malaria parasite lineage pLINN1 during single infection and the first report of this lineage in the fieldfare. The findings of multiple phanerozoites in brain, skeletal muscle, and eye tissue in combination with signs of vascular blockage and thrombus formation strongly suggest an impaired vision and neuromuscular responsiveness as cause of the unexpected collision with a slowly moving car. Further studies on exo-erythrocytic stages of haemosporidian parasites are pivotal to understand the true level of populational damage of avian malaria in wild birds.